Reduced-Fat Response of Lactobacillus casei subsp. casei SY13 on a Time and Dose-Dependent Model - Jia, Zhenhu; Pang, Xiaoyang; Lv, Jiaping (Frontiers in Microbiology, 2018)
As the reduced-fat effect of probiotics has been derived primarily from functional rather than structural, we investigated the ultrastructural aspects of the gut mucosa in Syrian golden hamsters with high-fat-diet by feeding Lactobacillus casei subsp, casei SY13 (Lc SY13). 36 adult male syrian golden hamsters were randomly allocated into four groups (control groupG1, high fat groupG2, higher dose groupG3, lower dose groupG4). The hamsters in G1 were fed a standard chow and those in other groups were fed a high-fat chow for 8 weeks. At the same time, the hamsters in G1 were received 1ML skim milk/hamsters/day by oral gavage and those in G3 and G4 were received Lc SY13 by oral gavage at 4.1×1010 or 4.1×108 cells/hamsters/day. At the 14d, 28d, 56d, three golden hamsters from every group were sacrificed by carotid, taking blood from eyeball for quantitative detection of hamsters serum total cholesterol (TC)、triacylglycerol (TG)、high-density lipoprotein (HDL) and low-density lipoprotein(LDL); at the same time, using Taqman-MGB fluorescence probe quantitative detection of Lc SY13 in intestinal contents at the 56d. The ileum of these hamsters was taken out for transmission electron microscopy (TEM). The result showed at the 56d ,the density of hamsters ileum microvilli in G3 was significantly bigger than other groups, but serum TC、TG and LDL level of the hamsters in G3 were decreased. Lc SY13 could be found in the intestinal. The number of them in ileum was significantly higher than that in G4. In conclusion, Lc SY13 may play a remarkable reduced-fat response role by improving the high-fat uptake, metabolism, and transport, especially in G3.The reduced-fat response of the Lc SY13 differed in a time- and dose- dependent manner. These findings indicated that probiotic strain of Lc SY13 can reduce fat level, suggesting its potential for improving obesity-related diseases.